Some coupled fixed point results for multi-valued nonlinear contractions in metric spaces using w-distance - Subhadip Roy; Parbati Saha; Choudhury Binayak S.; Rajendra Pant (Mathematica Moravica)
This study employs contractive criteria related to w-distances to design and address a non-linear multivalued fixed point problem. The results presented in this study are substantiated by the inclusion of three illustrative examples. In this work, a dedicated portion is allocated to the examination of the use of w-distances. Specifically, it explores how the utilization of w-distances in the current context expands upon the findings derived from metric distances.